Pengaruh Harga dan Lokasi terhadap Keputusan Pembelian pada Martabak Bangka Orcila 2, X - Sulis Fitriani; Ali Mubarok (Politeknik Kampar, 2025)
This study aims to analyze the influence of price and location on consumer purchasing decisions at Martabak Bangka Orcila 2, X. The background of this study is based on the increasingly fierce competition in the culinary business, so understanding the factors that influence consumers in making purchases is very important. The research method used is quantitative with an associative approach. A sample of 100 respondents was selected through probability sampling with the Slovin formula from a population of 21,437 consumers in 2024. Data analysis was carried out using simple and multiple linear regression, accompanied by correlation tests, coefficient of determination, t-tests, and F-tests to see the significance of the influence of variables.